ANALISIS PERBANDINGAN KINERJA ANTENA MIKROSTRIP PATCH LINGKARAN DAN BINTANG 27 PADA FREKUENSI 2.4 GHz - Akra, Faqiih; Purnomo, Muhammad Fauzan Edy; Kurniawan, Dwi Fadila (Jurnal Mahasiswa TEUB, 2024)
This study compares the performance of conventional circular patch and modified 27-star patch microstrip antennas, both operating at 2.4 GHz. Microstrip antennas are commonly used for their small size, though they have limitations such as low bandwidth. This research aims to improve antenna performance through geometric modifications and analyze the performance of the two antennas. Simulation results show that the 27-star patch achieves better return loss (-37.05 dB vs -35.31 dB) and superior bandwidth, while the circular patch performs better in real-world bandwidth tests (>4.2 GHz vs >4GHz). The circular patch exhibits a omnidirectional radiation pattern with elliptical polarization, whereas the 27-star patch shows a omnidirectional pattern with linear polarization. This study highlights the significance of geometric modifications and fabrication precision in enhancing microstrip antenna performance. Keywords: Microstrip antenna, Circular patch antenna, 27-star antenna, Antenna performance